Not always eosinophilic esophagitis – intramural pseudodiverticulosis of the esophagus – a case report and literature review - Frieling, Thomas; Kreysel, Christian; Blank, Michael; Mülle, Dorothee; Euler, Philipp; Melchior, Ilka (Zeitschrift für Gastroenterologie, 2020)
Background Intramural pseudodiverticulosis of the esophagus (EIPD) is a rare disease leading to dysphagia, chest pain, and weight loss. The diagnosis is difficult, and the disease can be confounded with eosinophilic esophagitis (EoE). We present a patient with esophageal intramural pseudodiverticulosis and a literature review.Case report The 45-year-old white caucasian woman with a history of nicotine and alcohol abuse had progressive hoarseness and severe dysphagia for solid food. Esophagogastroduodenoscopy (EGD) showed proximal esophageal stenosis, thrush esophagitis, and mucosal alteration with trachealization suspicious of EoE. However, repeated bouginage EGD and barium swallow revealed typical signs of esophageal intramural pseudodiverticulosis (EIPD). The patient was treated successfully by bougingage, acid suppression, and antifungal therapy. The literature analysis revealed the characteristics of EIPD according to age, sex, risk factors, and therapy modalities.Conclusion The case report and the literature overview suggest that EIPD can be confounded with EoE.
Keywords: dysphagia; regurgitation; noncardiac chest pain; esophageal intramural pseudodiverticulosis; eosinophilic esophagitis